SENYUM (SPECIAL NEED CHILDREN LIBRARY PROGRAM) - Istighfaroh, Asri Dzikrina; Mawaddah, Adzanishari; Pratiwi, Beta Bela; Masita, Anis Diah Ayu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
There are still many discrimination treatment aimed at Special Need Children, either in terms of social and educational, so it takes a special media which can facilitate the communities in accessing any information about Special Need Children. Special Need Children Library Program (SENYUM) is a library which can simplify communities in accessing any information about Special Need. This Program in collaboration with Autism Care Indonesia subdivisions Solo. SENYUM also conducts several activities, discussion forums, book mobile library, printing of journals and handbook, as well as writing and publishing a book entitled PELANGI. SENYUM has 950 copies of books and 265 members.